2009
DOI: 10.1186/1475-2875-8-118
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to compliance to anti-malarial drug combination: example of amodiaquine/sulphadoxine-pyrimethamine among children in rural Senegal

Abstract: Background: The introduction of new anti-malarial treatment that is effective, but more expensive, raises questions about whether the high level of effectiveness observed in clinical trials can be found in a context of family use. The objective of this study was to determine the factors related to adherence, when using the amodiaquine/sulphadoxine-pyrimethamine (AQ/SP) association, a transitory strategy before ACT implementation in Senegal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…A similar association was reported in Senegal, where it was concluded that older caregivers spent more time at home, could better attend to younger patients and knew more with regards to administering ACT [14]. It is likely that older respondents may have had prior experience administering or taking AL, which is supported by evidence from this study that indicates respondents who had seen AL before, had the odds 1.46 of adhering fully.…”
Section: Discussionsupporting
confidence: 81%
“…A similar association was reported in Senegal, where it was concluded that older caregivers spent more time at home, could better attend to younger patients and knew more with regards to administering ACT [14]. It is likely that older respondents may have had prior experience administering or taking AL, which is supported by evidence from this study that indicates respondents who had seen AL before, had the odds 1.46 of adhering fully.…”
Section: Discussionsupporting
confidence: 81%
“…Souares et al, revealed that, taste, cost and complexity were some of the most considered perspectives of patients in choosing a malaria drug during self-medication in their study in Senegal. 33 This can probably be the case in Ho.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have shown that non-prescribed anti-malaria drugs used by the majority of caregivers include chloroquine, amodiaquine, sulphadoxine-pyrimethamine and artemisinin-based combination therapy (ACT) and the dosage regimen taken are incorrect in most cases [4,5]. …”
Section: Introductionmentioning
confidence: 99%